2021
DOI: 10.1128/aem.00526-21
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Virus and Viral RNA in Relation to Surface Type and Contamination Concentration

Abstract: The transmission of SARS-CoV-2 is likely to occur through a number of routes, including contact with contaminated surfaces. Many studies have used RT-PCR analysis to detect SARS-CoV-2 RNA on surfaces but seldom has viable virus been detected. This paper investigates the viability over time of SARS-CoV-2 dried onto a range of materials and compares viability of the virus to RNA copies recovered, and whether virus viability is concentration dependant. Viable virus persisted for the longest time on surgical mask … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 32 publications
6
77
0
1
Order By: Relevance
“…Abrupt changes in hydration may be more disruptive than gradual changes [22]. Inactivation is particularly slow when droplets dry onto non-porous surfaces [71][72][73], for reasons that are not clear: water activity in surface deposits depends on ambient RH in the same way as in aerosol droplets large enough for the Kelvin effect to be ignored. Fractionation of solutes during surface drying [70,74,75] might lead to salt-free areas where the virus can survive in dried form at higher RH, or inactivation may occur at the air-water interface [76] or due to local capillary forces [77].…”
Section: Discussionmentioning
confidence: 99%
“…Abrupt changes in hydration may be more disruptive than gradual changes [22]. Inactivation is particularly slow when droplets dry onto non-porous surfaces [71][72][73], for reasons that are not clear: water activity in surface deposits depends on ambient RH in the same way as in aerosol droplets large enough for the Kelvin effect to be ignored. Fractionation of solutes during surface drying [70,74,75] might lead to salt-free areas where the virus can survive in dried form at higher RH, or inactivation may occur at the air-water interface [76] or due to local capillary forces [77].…”
Section: Discussionmentioning
confidence: 99%
“…The survival and persistence of SARS-CoV-2 on surfaces appear to be conditioned by characteristics of the material as well as temperature and humidity. A recent study [14] showed that UK SARS-CoV-2 strain, England 02/2020 remains viable for longer periods on hydrophobic surfaces (up to seven days) as compared with hydrophilic surfaces (three days).…”
Section: Introductionmentioning
confidence: 99%
“…Further differences in methodology that could affect the findings include the viral titre applied to the surface, which varies between studies (table 1). Paton et al [75] reported no significant difference ( p > 0.05) in SARS-CoV-2 decay on stainless steel between high (5.6 log 10 PFU) and low (3.6 log 10 PFU) inocula suggesting that inactivation is not associated with the viral load. Conversely, SARS-CoV-2 was detectable on paper for 30 min at 7.8 log 10 initial titre, with a 2.58 log 10 decline over this time period [11], compared to approximately 3.5 log 10 reduction over 5 days at 6.0 log 10 initial titre [74].…”
Section: Stability Of Coronaviruses On Porous Versus Non-porous Surfacesmentioning
confidence: 98%
“…The droplet spreads due to capillary action between the contact line and fibres present on the porous surface, resulting in a modified effective-wetted area due to the voids of porous materials, which leads to enhanced disjoining pressure within the film, thereby accelerating film evaporation [85]. The absorption of droplets within hydrophilic materials also spreads virions over a larger surface area which prevents aggregation [75]. Desiccation may lead to the viral lipid envelope undergoing phase changes and oxidation, and Maillard reactions may occur within proteins, rendering the virus noninfectious.…”
Section: Stability Of Coronaviruses On Porous Versus Non-porous Surfacesmentioning
confidence: 99%
See 1 more Smart Citation